1968
DOI: 10.1037/h0026185
|View full text |Cite
|
Sign up to set email alerts
|

Comparative psychological studies of Negroes and Whites in the United States: 1959-1965.

Abstract: This is a review of psychological studies concerning Negroes and whites in the United States for the most part from 1959 through 1965. The topics covered include: the physical substrata of psychological and psychosocial functions, physical and motor development, psychophysical functions, intellectual functions, educational and occupational attainment and aspirations, temperament, social perceptions and attitudes, mental illness, crime and delinquency, family organization. Research results from this period gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
2

Year Published

1969
1969
1981
1981

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(62 citation statements)
references
References 257 publications
(191 reference statements)
2
58
2
Order By: Relevance
“…6 The increased instances of acute brain syndrome in our non-white population may reflect the findings of others that alcoholism is more frequent in Negroes.6 The findings of assaultive and persecutory ideation and decreased depression in our homicidal non-white population may help account for the increased incidence of homicide and decreased incidence of suicide noted for American Negroes as a whole.237 Faris and Dunham ~ and Simon 12 have found a decreased incidence of depression in Negroes. Lane 10 has found the American Negro to score higher on process-reactive ratings.…”
Section: Religionmentioning
confidence: 67%
See 1 more Smart Citation
“…6 The increased instances of acute brain syndrome in our non-white population may reflect the findings of others that alcoholism is more frequent in Negroes.6 The findings of assaultive and persecutory ideation and decreased depression in our homicidal non-white population may help account for the increased incidence of homicide and decreased incidence of suicide noted for American Negroes as a whole.237 Faris and Dunham ~ and Simon 12 have found a decreased incidence of depression in Negroes. Lane 10 has found the American Negro to score higher on process-reactive ratings.…”
Section: Religionmentioning
confidence: 67%
“…Details of these studies are reported elsewhere. 16 6 We have also used our data in a multiple regression statistical formula to develop multiple regression equations for identification of patients with homicidal ideas, thoughts of assult, suicidal thoughts, delusions of persecution, and Examination. Multiple correlation co-efficients ranging from .25 to .48 on cross validated samples have been obtained.…”
Section: Use Of Correlations For Predictionsmentioning
confidence: 99%
“…Additional References: Baratz (1967); Clark (1967); Dreger and Miller (1968); Harris and Reitzel (1967); Harrison (1967).…”
Section: The Black Studentmentioning
confidence: 98%
“…The present subject population may be assumed, m general, to have experienced a relative deficit of white authonty-figure approval, this deficit being particularly pronounced m regard to achievement-oriented praise (Baron, 1970, Dreger & Miller, 1968. Given this assumption it should then follow that a relatively high level of praise from a white evaluator would be categorized as less appropnate than a relatively low level of praise.…”
mentioning
confidence: 97%